Ubanization In The Dki Jakarta Area Creates Slum Settlements - Nasruddin, Nasruddin (Journal of Multidisciplinary Science, 2022)
Increased urbanization always occurs in urban centers, this can affect changes in the form of bad regional planning such as the emergence of slum settlements. DKI Jakarta Province is the area with the fastest urbanization in Indonesia. Many residents from various regions come with various motives and different reasons, so it is very urgent for residential areas in DKI Jakarta which are very small and limited. The residential environment that is not supported by supporting facilities and high population mobility has caused many inappropriate settlements to be formed in DKI Jakarta Province. Inappropriate settlements or commonly referred to as slums are very influential on the level of environmental health in the region itself. Therefore, this study aims to determine how much influence urbanization has in creating slum settlements in the DKI Jakarta area with qualitative methods to collect data. In addition, what impact will happen to the population and the environment in DKI Jakarta Province if slum settlements continue to form? So that later it can provide solutions to problems that are following the contents of the existing problems.